Pension Provision for Muslim Clergy in Asian Part of Russian Empire (19th — Early 20th Century) - T. G. Nedzelyuk (Научный диалог)
The issue of granting pension benefits to Muslim clergy and their families in the Russian Empire is considered, as well as the characteristics of state-confessional policy in Russia both in the historical past and at the present stage. The aim of this study was to identify similarities and differences in the pension provision of Orthodox and Muslim clergy. Attention is paid to the socio-cultural status and material situation of clerics in border regions and national autonomies of the Asian part of Russia. Previously unstudied materials from the archives of the Russian State Historical Archive, the Russian State Historical Archive of the Far East, and the Central State Archive of the Republic of Kazakhstan are introduced into circulation. The novelty of the study lies in both the topic itself and the previously unexplored source base. Comparative, comparative-historical, and analytical research methods contributed to the realization of the research plan. The results obtained in the process of analyzing documents testify to a balanced approach and tolerant attitude towards clerics — representatives of “recognized” religions in the Russian Empire. The conclusion is formulated that the size of the pension depends on the length of service, but not on the religious affiliation of the clergy.